Evaluation of the Implementation of Arabic Language Learning for Postgraduate Masters Students at UIN STS Jambi / Evaluasi Pelaksanaan Pembelajaran Bahasa Arab Pada Mahasiswa Magister Pascasarjana UIN STS Jambi - Muhammad Qodri; Budi Sanjaya (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
This study aims to describe the evaluation of the implementation of Arabic language learning for Postgraduate Masters Students at the UIN STS Jambi. This study is evaluation research using a quantitative descriptive approach with survey methods. The data collection techniques used were direct observation, interviews and documentation. This research reveals that The implementation of Arabic language learning takes the form of in-depth and comprehensive understanding; students are invited to think independently, rationally, critically, analytically, after dissecting various Arabic literature. Assessment of learning outcomes is carried out through an assignment and exam mechanism, with components including individual and group assignment scores, student activity scores in class in answering questions. The results of the Arabic language proficiency test did not show very well, all indicators obtained a mean score interpretation that was still at a good stage (2.51 – 2.99). The highest results in the aspect of understanding (Mean=2.71, sd=0.88) with a good level percentage of 52.4% with a total of 33 respondents. The lowest mean score was in the aspect of answering accuracy (mean=2.49, sd=0.10) with a percentage at the poor stage of 11.1% with only 7 respondents at the very bad stage. 3). The aspect of understanding Arabic literature is in the poor category in understanding Arabic texts. Only 4 people or 3.6% of respondents were able to understand the text very well. 8 people or 12.7% of respondents did not really understand Arabic texts. Of the total 63 respondents, only 31 people or 49.2% of respondents were able to understand Arabic literature well.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan evaluasi pelaksanaan pembelajaran bahasa Arab di Pascasarjana UIN STS Jambi. Penelitian ini merupakan penelitian evaluasi dengan menggunakan pendekatan deskriptif kuantitatif dengan metode survei. Teknik pengumpulan data yang digunakan adalah observasi langsung, wawancara dan dokumentasi. Penelitian ini mengungkap bahwa Pelaksanaan pembelajaran bahasa Arab berbentuk pemahaman mendalam dan komprehensif, mahasiswa diajak untuk berpikir mandiri, rasional, kritis, analitis, setelah membedah berbagai literatur bahasa Arab. Penilaian hasil belajar dilakukan melalui mekanisme penugasan dan ujian, dengan komponen meliputi nilai tugas individu dan kelompok, nilai aktivitas mahasiswa di kelas dalam menjawab soal. Hasil tes kemampuan bahasa Arab belum menunjukkan sangat baik, semua indikator memperoleh interpretasi skor rata-rata yang masih pada tahap baik (2,51 – 2,99). Hasil tertinggi pada aspek pemahaman (Mean=2,71, sd=0,88) dengan presentase tingkat baik sebesar 52,4% dengan jumlah responden 33 orang. Nilai rata-rata terendah terdapat pada aspek ketepatan menjawab (mean=2,49, sd=0,10) dengan presentase pada tahap kurang baik sebesar 11,1% dengan hanya 7 responden yang berada pada tahap sangat kurang. 3). Aspek pemahaman literatur berbahasa Arab berada pada kategori kurang baik dalam memahami teks bahasa Arab. Hanya 4 orang atau 3,6% responden yang mampu memahami teks dengan sangat baik. Sebanyak 8 orang atau 12,7% responden tidak begitu memahami teks bahasa Arab. Dari total 63 responden, hanya 31 orang atau 49,2% responden yang mampu memahami literatur berbahasa Arab dengan baik.